2006
DOI: 10.1159/000096357
|View full text |Cite
|
Sign up to set email alerts
|

Incidental Thyroid Carcinoma in Thyrotoxic Patients Treated by Surgery

Abstract: Background and Aims: Thyroid malignancy detected incidentally in patients who are operated for thyrotoxicosis has been reported at different rates. The aim of this study was to investigate the rate of incidental thyroid carcinoma in thyrotoxic patients managed with surgery in our institution. Methods: Of the 375 thyrotoxic patients who had thyroid surgery between the years of 1997–2004, 70.7% were females and 29.3% were males. Among thyrotoxic patients 65.3% (n = 245) had toxic multinodular goiter (TMG), 16.8%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 39 publications
1
9
0
1
Order By: Relevance
“…These data suggest that Del403 is likely a new active TSHR mutation, but further in vitro studies are required. With respect to the prevalence of a germline polymorphism of Asp727Glu in the TSHR gene and the presence of incidental papillary thyroid carcinoma in thyroid surgical specimens, our results confirm the findings of previous studies [32][33][34].…”
Section: Acknowledgmentssupporting
confidence: 89%
“…These data suggest that Del403 is likely a new active TSHR mutation, but further in vitro studies are required. With respect to the prevalence of a germline polymorphism of Asp727Glu in the TSHR gene and the presence of incidental papillary thyroid carcinoma in thyroid surgical specimens, our results confirm the findings of previous studies [32][33][34].…”
Section: Acknowledgmentssupporting
confidence: 89%
“…This was not surprising. Papillary microcarcinomas, defined as tumours of 1 cm or less, are common incidental findings in a nodular goitre or in the thyroid glands of Graves’ disease 37,38 . In this study they were 2 and 3 mm, respectively, and unlikely to have shown any clinical symptoms.…”
Section: Discussionmentioning
confidence: 60%
“…Concerning associated thyroid diseases, multinodular goiter appear to have the highest incidence, from 4% to 17% (43,44). In Graves, the incidence varies from 0.5% to 1.8% (45)(46)(47)(48)(49). The incidence of carcinomas in the cervicomediastinal goiter compared with benign thyroid cervical-mediastinum disease, is around 12.1% (50,51).…”
Section: Discussionmentioning
confidence: 99%